(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This scientific article examines the use of educational game platforms (such as EduGames.uz and similar ones) for developing students’ creative competencies in higher education institutions through the interactive organization of the learning process. The work highlights the advantages of the game-based learning approach, its role in enhancing creativity, and provides practical examples.